TRANSITIVITY ANALYSIS OF LYDIA MACHOVA’S SPEECH IN TED TALKS: A SYSTEMIC FUNCTIONAL LINGUISTICS STUDY - Hastuti, Erni; Setiawati, Apriliasih; Oswari, Teddy (Journal of Language and Literature, 2021)
The research focus is a systemic functional linguistics study especially analysis of transitivity systems used by Lydia Machova in speech The Secret of Learning a New Language TED Talks. The research objective is to find out the types of transitivity process identified by Lydia Machova in her speech of The Secret of Learning a New Language in TED TALKS based on the theory proposed by Halliday (2004). This research used descriptive qualitative research. The datas are clauses in form of simplex and complex clauses which provided the types of transitivity process. The research result shown all types of transitivity process in Lydia Machova utterances. The highest usages of transitivity process are Material process due to the most accessible to our conscious reflection and the function of doing process in Lydia context of discussion is positively influence the listeners to follow the tips and the advice which Lydia and other polyglots experienced in learning language processes.